Nanosatellite thermal state under nonstationary heat generation from payload radio-electronic elements - S. V. Belov; A. V. Belkov; A. P. Zhukov; M. S. Pavlov; S. V. Ponomarev (Космические аппараты и технологии, 2024)
The purpose of the work is to assess the thermal operating conditions of the radio-electronic components of a nanosatellite under orbital flight conditions. The following article presents the numerical research results involving the thermal state of 1U CubeSat nanosatellite in the course of its motion at low-Earth orbit (at the height of 300km) during autumnal equinox and winter solstice days. The nanosatellite numerical thermal model includes the heat rate from the Sun and Earth surface, and, at the same time, excluding atmospheric temperature rise. Moreover, nonstationary heat generation from nanosatellite payload of radio-electronic elements, as well as energy re-radiation within the nanosatellite casing itself are taken into account. The nanosatellite geometry, structure, thermal-physical material properties and free surface optical properties as well as its payload operational mode estimations are based on reliable literature references. The numerical model results indicate the fact that the radio-electronic element temperature depends on its heat generation rate output, thermal radiation of adjacent circuit boards, low-Earth orbital nanosatellite motion and its orbital position. Radio-electronic element temperature dynamics is determined by the acting heat generation regimes. Although, under conditions of the formulated problem, the temperature of most radio-electronic elements is within the acceptable operation limits, nevertheless, rapid high-level thermal load impact could result in excessive heating of the payload elements.